Variational Approximation for Modified Meyer-König and Zeller Operators - Taş, Emre; Yurdakadim, Tuğba (Sarajevo Journal of Mathematics, 2022)
In the present paper we introduce modified Meyer-König and Zeller operators which coincide with the classical Meyer-König and Zeller operators if $ω(x)=x$. We provide sufficient conditions on the boundedness of the total variation of these operators and we also present a result which deals with the variational approximation of the new modified operators.